Effects of Mg2+, Fe3+, Mn2+ and Cu2+ Ions on Lipid Accumulation by Cunninghamella bainieri 2A1 - Manikan, V; Kalil, MS; Omar, O; Kader, AJA; Hamid, AA (Univ Kebangsaan Malaysia, 2024)
Indexed by WOS/Scopus